Medium term impacts of sovereign rating changes on financial stability - Shahrivar, Hesam Aldin (International Economic Society ies@econ-society.org, 2012)
This study aims to investigate the relation of sovereign rating announcements and financial market. Therefore in this study we examine the role of sovereign rate changes in fluctuations of financial markets. In order to find this relation an Index of Speculative Market Pressure has been created and used in twenty emerging economy countries. We aimed to analyze the role of rating agencies in international financial market. In this study we used ARMA model to calculate the abnormal jumps of financial market index, speculative market pressure, and run event study. Results of this empirical imply that credit rating agencies do have medium-term impact on financial markets of emerging countries. © International Economic Society.
Keywords: ARMA model; Event study; Sovereign credit rating; Speculative market pressure